Gendered Participation in Elementary Science Learning: Understanding Stereotypes and Lived Experiences: - - Fitria Khusnul Khotimah; Welius Purbonuswanto (Jurnal Penelitian Pendidikan IPA, 2026)
In many elementary classrooms, boys and girls often engage in natural science in different ways. This study explores how students, teachers, and parents perceive these differences in South Klaten, Klaten, Central Java through a qualitative phenomenological approach. Data were gathered through interviews, participant observation, and student journals involving 30 students, 10 teachers, and 10 parents. The findings show the common view that girls tend to prefer biological topics that involve patience and verbal explanation, while boys are more drawn to experiments and physical science tasks. Thematic analysis identified three key points: differences in the understanding of science concepts based on gender, the influence of gender stereotypes on motivation and participation, and the role of the social and cultural environment in shaping students’ views of science. The study concludes that perceived gaps in science learning reflect social construction rather than innate ability and encourages classroom strategies that reduce stereotype reinforcement and expand opportunities for participation.